2007
DOI: 10.1017/s1479262107710870
|View full text |Cite
|
Sign up to set email alerts
|

Allelic diversity of natural oil palm (Elaeis guineensis Jacq.) populations detected by microsatellite markers: implications for conservation

Abstract: The allelic diversity within oil palm populations (45 native ones from 10 African countries, three breeding populations and one collection of semi-wild material) was determined using 16 microsatellite markers. A total of 209 alleles were detected, with a mean number of 13.1 alleles per locus. The mean effective number of alleles per locus (A e ) was 3.3^1.3. Although the Duncan's multiple range test only separated the group of populations from Madagascar from the rest on the basis of A e , the presence of uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 5 publications
2
24
1
2
Order By: Relevance
“…However, the low genetic distance (D R = 0.2000) observed between NIFOR dura AD5 from Aba and Angola accession G-AG2 maintained at MPOB germplasm, may indicate that the oil palms from the two geographical zones might have been derived from similar genetic background. Similar observation was reported by Bakoumé (2006). The dendogram showed total divergence of oil palm material from Madagascar from all other materials evaluated in this study.…”
Section: Genetic Differentiation and Relatedness Among Nifor And Mpobsupporting
confidence: 90%
“…However, the low genetic distance (D R = 0.2000) observed between NIFOR dura AD5 from Aba and Angola accession G-AG2 maintained at MPOB germplasm, may indicate that the oil palms from the two geographical zones might have been derived from similar genetic background. Similar observation was reported by Bakoumé (2006). The dendogram showed total divergence of oil palm material from Madagascar from all other materials evaluated in this study.…”
Section: Genetic Differentiation and Relatedness Among Nifor And Mpobsupporting
confidence: 90%
“…In fact, Augustina et al [73] reported a total of 163 alleles (mean = 8.2) among the 85 pisifera accessions from germplasm collections of different origins at Sampoerna Agro Tbk (SA) in Indonesia. Bakoumé et al [37] detected a total of 209 alleles, with a mean number of 13.1 alleles per locus in a sample of 494 oil palm derived from 10 African countries. Cochard et al [8] obtained a total of 202 alleles, with an average of 14.5 alleles per locus within 318 oil palm samples from eight countries.…”
Section: Mean Number and Effective Number Of Alleles Per Locusmentioning
confidence: 99%
“…Several studies have shown a general tendency of loss of diversity after several cycles of selection. In a related study, Bakoumé et al [37] investigated the allelic diversity of 3 breeding materials, using 16 microsatellite markers and observed that rare alleles were common alleles in wild oil palm populations showing a reduction due to many years of selection in the materials.…”
Section: Mean Number and Effective Number Of Alleles Per Locusmentioning
confidence: 99%
“…É necessário analisar a diversidade genética das progênies de dendezeiro tipo Dura, de origem Deli, que têm base genética estreita e são utilizadas como fonte exclusiva de genitores Dura das cultivares produzidas atualmente, para orientar sua diversificação no programa de melhoramento. Nesse sentido, marcadores moleculares podem ser usados no estudo da diversidade genética de germoplasma, selvagem ou melhorado, o que pode dar suporte à conservação e ao melhor uso no programa de melhoramento da espécie (Hayati et al, 2004;Maizura et al, 2006;Bakoume et al, 2007;Cochard et al, 2009;Vieira et al, 2009).…”
Section: Introductionunclassified